Effect of planting dates on crop growth indices and yield of different rice varieties - Harithalekshmi V.; B. Ajithkumar; P. Lincy Davis; Arjun Vysak (Annals of Agricultural Research, 2023)
The present study was done to examine the influence of weather conditions created by different dates of planting on rice growth and yield of two different rice varieties Jaya and Jyothi. The experiment was laid out using split plot design with five planting dates as June 5th, June 20th, July 5th, July 20th, and August 5th as the main-plot treatments and the two rice varieties viz. Jyothi (short duration) and Jaya (medium duration) as sub-plot treatments with four replications. Plant height was measured at weekly intervals. Leaf area and dry matter were measured at fortnightly intervals. With these data, growth indices viz. leaf area index, leaf area duration, crop growth rate, and net assimilation rate were calculated for both Jyothi and Jaya. Yield and yield attributes were also measured. Results showed that leaf area index and duration were increasing towards the maturity and were highest during 75 days after planting for both the varieties. The crop growth rate was found to be increasing up to 45-60 days, thereafter it showed a decreasing value. During this period maximum crop growth rate was seen for August 5th planting. The net assimilation rate was highest during 15-30 days after planting and was decreasing towards maturity period. It was also found that both dates of planting and variety are having significant influence on yield and yield attributes. Various weather conditions created under different planting dates may have influenced the crop growth rate.